Management Functions vs. Budgeting Process - Kes, Zdzisław; Dynowska, Joanna (Funkcje zarządzania a proces budżetowania, 2011)
This paper answers questions regarding how phases of budgeting support management functions. It explores the relationship between phases of budgeting i.e. creating, realizing and controlling budgets and management functions i.e. planning, organizing, incentivizing and controlling. For these four management functions, the research establishes that planning, incentivizing and controlling are directly supported by the budgeting process, whereas organizing is not directly associated with the budgeting process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 39-48
Keywords: budgeting; management functions; budgeting process